THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK DISCIPLINE ON PUBLIC SERVICE QUALITY (A CASE STUDY AT SEKOTONG TENGAH VILLAGE, SEKOTONG DISTRICT, WEST LOMBOK REGENCY) - Jafar Idrus; Andi Nugraha; Adi Suroso (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine whether transformational leadership and work discipline simultaneously influence the quality of public services, as well as to investigate the individual effects of each variable on service quality. A total of 50 respondents participated in this study, comprising village officials and community members working within the administrative environment of Sekotong Village, Sekotong District. Data were collected using a saturated sampling method through questionnaire distribution and library research, then analyzed using multiple linear regression with the assistance of SPSS 27. The findings reveal three key conclusions: first, transformational leadership has a significant effect on the quality of village public services; second, work discipline similarly affects service quality; and third, both transformational leadership and work discipline together exert a significant combined influence on the quality of village public services.